Assessment of E-Learning in Institutions of Higher Learning in Uganda: A Case Study at Kabale University. - Nabaasa, Scovia (Kabale University, 2024)
The research aimed to determine the effects of e-learning at Kabale University. Conducted at Kabale University, the study utilized quantitative methods for data collection and analysis, employing questionnaires and interviews. The findings revealed that many students and lecturers were using e-learning for studying and curriculum delivery. However, both groups encountered several challenges with e-learning approaches, and various measures were being implemented to address these issues. Additionally, the study identified several factors that supported e-learning at Kabale University.